Reflections on cultures, languages and education: An urgent debate (Revista Contexto & Educação, 2025)
This work is part of an ongoing doctoral research that investigates how the educational project is constituted in rural territories with a strong presence of descendants of Germanic immigrants. Based on the concept of dialogicity, grounded in the studies of Bakhtin (2010) and Freire (2013), the research aims to analyze how the culture and languages of students from three rural community schools manifest themselves in school time and space. We juxtapose the concepts of culture and interculturality from Forquin (1993) and Candau (2002) with studies on linguistic rights, bilingualism, plurilingualism, and language contact by Altenhofen (2004) and Savedra (2021). In Gramsci (2004) and Semeraro (2006), we find support for understanding the teacher's work as an organic intellectual capable of problematizing and establishing a dialogical relationship between the community's cultural context and the knowledge established by educational legislation. The methodology used for this production is based on a literature review of the aforementioned authors and leads us to consider that cultures and languages pose challenges in the schooling process and have the power to foster the construction of an educational project that considers the rural and plurilingual territory of the students.
Keywords: culture; languages; education; dialogicity